2022
DOI: 10.1142/s0218625x22500445
|View full text |Cite
|
Sign up to set email alerts
|

WEAR PROPERTIES AND MICROSTRUCTURE OF WC–10Co–4Cr POWDER COATING APPLIED TO CULTIVATOR BLADES VIA HVOF

Abstract: Abrasion of cultivator equipment parts working in the soil causes serious losses if necessary precautions are not taken. The cultivator blades used to plow the soil in agricultural production wear out over time. In order to reduce this wear, the hardness and wear resistance of the material should be increased first. In this study, some of the 30MnB5 cultivator blades were heat-treated and some were coated with HVOF technique. The samples were obtained by plowing the soil at 15-cm working depth and 5.4-km[Formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…However, they cannot sufficiently increase the performance of high-tech, high-capacity cultivation implements. In particular, in order to extend the economic life of cultivator blades and achieve high productivity, [5][6][7] scientists have investigated different practical techniques such as carburizing, nitriding, carbonitizing, 8,9 and boriding. 10 Scientists have from time to time also used various surface quality improvement techniques such as thermal spray coating, surface hardening, electrodeposition, melting of flux-cored wires and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they cannot sufficiently increase the performance of high-tech, high-capacity cultivation implements. In particular, in order to extend the economic life of cultivator blades and achieve high productivity, [5][6][7] scientists have investigated different practical techniques such as carburizing, nitriding, carbonitizing, 8,9 and boriding. 10 Scientists have from time to time also used various surface quality improvement techniques such as thermal spray coating, surface hardening, electrodeposition, melting of flux-cored wires and others.…”
Section: Introductionmentioning
confidence: 99%
“…However, they cannot sufficiently increase the performance of high-tech, high-capacity cultivation implements. In particular, in order to extend the economic life of cultivator blades and achieve high productivity, 57 scientists have investigated different practical techniques such as carburizing, nitriding, carbonitizing, 8,9 and boriding. 10…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, iron carbides in the form of black colonies appear to have an irregular morphology. In a similar study, Singh et al [38] and [4,[24][25][26] observed pearlitic, ferritic, and cementitic phases for steels with the same microstructure. As shown in figure 7, x-ray Diffraction Analysis Confirmed The Presence of cementite and ferrite phases in this material.…”
Section: Resultsmentioning
confidence: 73%
“…Therefore, a protective coating on the surface can be a practical solution. Thermal spraying is the most common surface technology for applying wear protection coatings [7,[18][19][20][21][22][23][24][25][26], with atmospheric plasma spraying (APS) being the most practical of the thermal spraying techniques [17,27].…”
Section: Introductionmentioning
confidence: 99%
“…The hardfacing is considered as economical way to improve the performance of components submitted to severe wear conditions, with wide range of applicable filler materials [29,30,31,32]. Among the methods of applying a wear-resistant layer by the method of hardfacing, the following IOP Publishing doi:10.1088/1757-899X/1277/1/012016 2 were most widely used: shielded metal arc or manual metal arc welding (SMAW or MMAW) [33], gas metal arc welding (GMAW), submerged arc welding (SAW), self-shielded flux-cored arc welding (FCAW-S) [34,35,36,37].…”
Section: Introdactionmentioning
confidence: 99%